Overexpression of bacterial ethylene-forming enzyme gene in Trichoderma reesei enhanced the production of ethylene - Xi Chen, Yong Liang, Jing Hua, Li Tao, Wensheng Qin, Sanfeng Chen (International Journal of Biological Sciences, 2010)
In order to efficiently utilize natural cellulose materials to produce ethylene, three expression vectors containing the ethylene-forming enzyme (efe) gene from Pseudomonas syringae pv. glycinea were constructed. The target gene was respectively controlled by different promoters: cbh I promoter from Trichoderma reesei cellobiohydrolases I gene, gpd promoter from Aspergillus nidulans glyceraldehyde-3-phosphate dehydrogenase gene and pgk I promoter from T. reesei 3-phosphoglycerate kinase I gene. After transforming into T. reesei QM9414, 43 stable transformants were obtained by PCR amplification and ethylene determination. Southern blot analysis of 14 transformants demonstrated that the efe gene was integrated into chromosomal DNA with copy numbers from 1 to 4. Reverse transcription polymerase chain reaction (RT-PCR) analysis of 6 transformants showed that the heterologous gene was transcribed. By using wheat straw as a carbon source, the ethylene production rates of aforementioned 14 transformants were measured. Transformant C30-3 with pgk I promoter had the highest ethylene production (4,012 nl h-1 l-1). This indicates that agricultural wastes could be used to produce ethylene in recombinant filamentous fungus T. reesei.